The Impact of Digital Talent Management on Employee Performance with Individual Innovation Behavior as Intervening Variable at PT Dakwah Inti Media - Sonda, Anggun Langitry; Kistyanto, Anang (CV ODIS, 2023)
The purpose of this study was to analyze the effect of digital talent management on employee performance with individual innovation behaviour as an intervening variable. This research is causality research with a quantitative approach. The sampling technique used saturated samples with a total of 54 respondents at PT Dakwah Inti Media. The statistical analysis used in this research is partial least square with the help of SmartPLS 3.2.9 software. The result of the analysis obtained from this study indicates that digital talent management has a positive and significant effect on employee performance; digital talent management has a positive and significant effect on individual innovation behaviour; individual innovation behaviour has a positive and significant effect on employee performance; individual innovation behaviour in this study can mediate the effect of digital talent management on employee performance.